On combinational contractions with applications - Mohammed Shehu Shagari; Manzuma Mustapha; Hala H. Taha; Sarah Aljohani; Nabil Mlaiki (Heliyon)
The aim of this paper is to provide a new hybrid contraction that is a combination of Jaggi, Meir-Keeler and Zamfirescu-type contractions in the framework of a complete metric space. The existence and uniqueness conditions of a fixed point of such contractions are investigated. An example is constructed to demonstrate the validity of the obtained results. Furthermore, the presented result is utilized to formulate new criteria for solving a class of nonlinear Fredholm integral equation.